2012
DOI: 10.1111/j.1468-0351.2012.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric trade protection leading not to productivity but to export share change

Abstract: This article revisits a classical theme in economics, that is, the relationship between trade protection and economic performance, with an improved treatment of the endogeneity of tariffs and with consideration of alternative performance criteria. This paper also considers the effects of asymmetric protection, such as higher tariffs on consumer goods and lower tariffs on producer goods. Using sectoral data on Korean manufacturing during the period from 1967 to 1993, this study finds that the effect of trade pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…In other words, industrial policy is now to be understood not merely as promoting manufacturing industries, but also promoting modern production and service activities in general (Cornia and Vos, 2013). Empirical research, such as those by Aghion, Dewatripont, Du, Harrison, and Legros (2011) and Shin and Lee (2012), verify the positive eff ect of industrial policy in contrast to earlier literature that found its eff ect to be insignifi cant, such as in the work of Beason and Weinstein (1996) or Lee (1996).…”
Section: Introductioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In other words, industrial policy is now to be understood not merely as promoting manufacturing industries, but also promoting modern production and service activities in general (Cornia and Vos, 2013). Empirical research, such as those by Aghion, Dewatripont, Du, Harrison, and Legros (2011) and Shin and Lee (2012), verify the positive eff ect of industrial policy in contrast to earlier literature that found its eff ect to be insignifi cant, such as in the work of Beason and Weinstein (1996) or Lee (1996).…”
Section: Introductioncontrasting
confidence: 39%
“…One reason for the mixed outcome of industrial policy may be the diffi culty of verifying the average positive eff ect of industrial policy because the eff ects tend to appear only under certain conditions, depending upon specifi c contexts (Shin and Lee, 2012). Th us, the OECD (2013) concludes that the three basic ingredients for successful industrial policies are investment in skills, access to fi nancing, and adequate infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…A desirable structure of tariff may be asymmetric structure, such as higher tariffs for sectors that are being promoted and lower tariffs for imported capital goods. Such asymmetric tariffs increased the world market share of Korean products (Shin and Lee 2012). Other forms of horizontal interventions are needed to build physical infrastructure.…”
Section: Stages Of Learning and Capability-buildingmentioning
confidence: 99%
“…The first is that judgment about the effectiveness of such policy always depends on the goals and criteria for judgment. For instance, regarding industrial policy, Shin and Lee (2012) find that while tariffs in Korea in the 1960s and 1970s were not successful in increasing total factor productivity (which is a conventionally adopted measure of assessment in the literature), they have been very successful in increasing the volume of exports or market share of Korean exports, which implies that the government in charge of industrial policy did not aim to increase efficiency but rather scale, which can help to reduce costs and increase market share. This issue of what are the criteria for success seems not to have been addressed much in this book.…”
mentioning
confidence: 99%